COMPRESSIVE ANALYSIS OF MULTI-INFILL LATTICE STRUCTURE PARTS 3D PRINTED BY FDM - Noor Faraz Khan; Dr. Abdul Shakoor; Muhammad Bilal Afzal; Atif Shehzad (Spectrum of Engineering Sciences, 2025)
This study investigates the failure mechanisms of multi-infill lattice structures fabricated using Fused Deposition Modeling (FDM) under compressive loading. Leveraging a combination of Gyroid and Cubic infill geometries, seven stacking configurations—including both pure and hybrid designs—were 3D printed using PLA+ material. The mechanical performance and failure modes of these configurations were evaluated through standardized compression tests, following ASTM D695 guidelines. Results reveal that stacking sequence, interlayer transitions, and pattern geometry significantly influence the mode and progression of failure. Specimens with Gyroid infill exhibited progressive and ductile failure, while Cubic-dominant designs failed in a brittle and localized manner. Hybrid patterns, particularly those with alternating Gyroid-Cubic layers, showed a combination of ductile and brittle failure characteristics. The study provides critical insights into the design of structurally resilient components for engineering applications requiring high compressive strength and energy absorption